The Poplar Rust-Induced Secreted Protein (RISP) Inhibits the Growth of the Leaf Rust Pathogen Melampsora larici-populina and Triggers Cell Culture Alkalinisation - Petre, Benjamin; Hecker, Arnaud; Germain, Hugo; Tsan, Pascale; Sklenar, Jan; Pelletier, Gervais; Séguin, Armand; Duplessis, Sébastien; Rouhier, Nicolas (Frontiers in Plant Science, 2016)
Plant cells secrete a wide range of proteins in extracellular spaces in response to pathogen attack. The poplar rust-induced secreted protein (RISP) is a small cationic protein of unknown function that was identified as the most induced gene in poplar leaves during immune responses to the leaf rust pathogen Melampsora larici-populina, an obligate biotrophic parasite. Here, we combined in planta and in vitro molecular biology approaches to tackle the function of RISP. Using a RISP-mCherry fusion transiently expressed in Nicotiana benthamiana leaves, we demonstrated that RISP is secreted into the apoplast. A recombinant RISP specifically binds to M. larici-populina urediniospores and inhibits their germination. It also arrests the growth of the fungus in vitro and on poplar leaves. Interestingly, RISP also triggers poplar cell culture alkalinisation and is cleaved at the C-terminus by a plant-encoded mechanism. Altogether our results indicate that RISP is an antifungal protein that has the ability to trigger cellular responses.